An annotated catalogue of bird lice (Insecta: Phthiraptera) from Chile - González-Acuña, Daniel A.; Palma, Ricardo L. (Zootaxa, 2021)
The species and subspecies of chewing lice (Insecta: Phthiraptera: Amblycera, Ischnocera) parasitic on Chilean birds are listed and annotated, based on records published until October 2021 and from our examination of collections. The current scientific name, its taxonomic history, data on type material, type host, other hosts, geographic distribution within Chile and elsewhere, Chilean literature references and other significant references are given for each species or subspecies of lice. A total of four families, 76 genera, and 245 species and subspecies of lice are listed, including 17 species recorded as genus only, and 31 new records of species. A host-louse list—including a total of 155 bird species (146 native and nine introduced by human agency) belonging to 19 orders, 43 families and 107 genera—is also given.